Relación entre la inversión pública y el valor agregado bruto de la región Loreto, período 2016-2020 - Freitas Saavedra, Xiomy Liliana (2022)
In the last decade, the productive structure of the Loreto region was based mainly on extractive activities, added to commercial, cultivation and breeding activities, which contain little added value, but still contribute to the region's GVA. The objective of this thesis is to determine the relationship between Public Investment and Gross Added Value of the Loreto region, period 2016 - 2020, for this, the present Correlational and Non-Experimental design investigation was carried out, analyzing the Public Investment of the National Government, in the expense accrued by the Acquisition of Non-financial Assets of the Loreto region, highlighting that during the last quarters of the years 2018 and 2020 the highest expenses in public investment were presented, reaching amounts of S/ 152,908,342.00 and S/ 122,231,399 respectively. On the other hand, the most important economic activity in the conformation of the GVA of the Loreto region, during the first biennium of the analysis period, was "Commerce" concentrating 19.23% and 18.22% for the years 2016 and 2017 respectively; to then be the activity "Extraction of Oil, Gas and Minerals" which predominates in the last three-year period of the same period of analysis, concentrating 18.40%, 19.97% and 19.97% for the years 2018 to 2020 respectively.